Análise da implantação de uma central de liquidação de despesas na controladoria geral do município de São Luís-Maranhão - Silva, Flávio Olimpio Neves (2010)
The Federal Constitution demands the requirement of accounting, financial, budgetary, operational investigatory in public administration, through internal and external control. Within the city of São Luís, internal control is performed by the General Controllership of the Municipality, through the auditing, supervision and guidance. Thus, the aim of the present work analyze the contribution of the implementation of the Central Unit of Expenses under the São Luís city General Comptrollership regarding the control of public spending. the work was initially carried out a bibliographic research on control in government and the powers of the organs, specifically the General Comptrollership of the Municipality of São Luís. Then there was a field research, analyzing legislation and others regulations on internal control of the city and then questionnaires with the servers for data collections on the functioning of the Central Payment of Expenses. After collection, the data were analyzed and studied, the results demonstrated through a written report with the aid of tables, charts and graphs. At the end, it was possible to outline the functioning of the Central Payment of Expense, the relationship of the auditors with the city managers and highlight the major deficiencies identified in public expenditure was found that City of São Luís has a system of internal control expenditure able to block the payment with evidence of irregularities, allowing the body of internal control knowledge before payment, the estate of all expenditure of incurred by the managers, showing that the Central Settlement of Expenditures has a significant role in the public municipal for the guidance and supervision in relation to the actions of administrators, in order to ensure the appropriate use of public resources. However, we must improve it in some places, to become effective the internal control model integrated in the public hall of São Luis, adopting corrective measures or complementary to adapt and integrate all the stages of formalization of the expenditure for the internal control system. Otherwise, it will perpetuate the routine of the central body to relate to inadequacies, to point out deficiencies, make recommendation and produce new improprieties.